The internationalization of firms from India. - Nayyar, D (QEH (University of Oxford), 2007)
The object of this paper is to analyze the rapid expansion in outflows of foreign direct investment from India and the spurt in foreign acquisitions by Indian firms, during the past decade, situated in the wider context of international investment from developing countries. It finds that the sectoral-composition and geographical distribution of outward foreign direct investment from India provides two sharp contrasts with that from developing countries: much of it was in manufacturing activities and most of it was in industrialized countries. These characteristics were mirrored in the pattern of foreign acquisitions by Indian firms. The economic stimulus and the strategic motive for the internationalization of firms from India was provided by a range of underlying factors driving the process: market access for exports, horizontal or vertical integration, delivery of services, capturing international brand names, access to technology, sourcing raw materials and global leadership aspirations. The significance of these factors differs across sectors, even firms. It is clear, however, that the rapid growth in foreign direct investment outflows from India that began circa 2000 and the spurt in foreign acquisitions by Indian firms that began circa 2005 were both, in part, attributable to the conjunctural factors implicit in the liberalization of the policy regime and the greater access to financial markets. But it must be recognized that Indian firms could not have become international without the capacity and the ability to compete in the world market. The attributes of Indian firms, which created such capacities and abilities, are embedded in the past and have emerged over a much longer period of time. This internationalization of firms from India has economic implications, both positive and negative, at a microlevel for firms and at a macro-level for the economy.